Effect of zinc oxide addition in slag system and heating manner on boron removal from metallurgical grade silicon. (January 2017) - Wu, Jijun; Xia, Zhenfei; Ma, Wenhui; Wang, Fanmao; Zhou, Yeqiang; Wei, Kuixian
Abstract: Different amount of ZnO was added to calcium silicate reagent to improve boron removal from metallurgical grade silicon (MG-Si). The thermodynamic analysis showed that the reagent CaO-SiO2 -ZnO had a stronger ability to boron removal than the reagent CaO-SiO2 . Two kinds of heating manners of electromagnetic induction and resistance were used to refine MG-Si. Compared with the resistance heating, the induction heating showed a much higher efficiency of boron removal. The mechanism of boron removal from MG-Si by ternary CaO-SiO2 -ZnO slag reagent was put forward and the role of ZnO in slag to boron removal was described. The by-product Zn in refined silicon can be thoroughly removed by a vacuum distillation treatment, which showed an absolute advantage to the residual zinc removal in silicon by comparison with the acid leaching treatment. The residual zinc in silicon was reduced to lower than 0.05 ppmw after a vacuum treatment at 1723 K.